(untitled) (Analysis in Theory and Applications, 2017)
In this paper, we show that new modified double cosine trigonometric sums introduced in [1] are inappropriate, the class of double sequences J_d introduced there is unusable for such sums and consequently the results obtained in it are completely incorrect. We here introduce appropriate modified double cosine trigonometric sums making the class J_d usable considering a particular double cosine trigonometric series.